Pemodelan Dan Rekomendasi Proses Bisnis Menggunakan Metode Business Process Improvement (BPI) (Studi Kasus: NGALUP.CO) - Deafinansia Nurido Andiyani; Nanang Yudi Setiawan; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Ngalup.co is the company engaged in creative industry area. Ngalup.co found that there are several processes that are not carried out according to the procedure, so that it's implemented inappropriately. Indications that occur are booking hall events that took a long time and needs a lot of resources, so that the process business often missed. Based on the indication problems, this study was conducted to evaluate business processes and to analyze the potential problem and the root of problem that occurs in business process at Ngalup.co and then given the recommendation for improvement of business process. This study uses Business Process Modeling and Notation (BPMN) diagram and Failure Mode and Effect Analysis method (FMEA) to analyze and evaluate business process, and Business Improvement Method (BPI) to do improvement. From the results of simulations carried out in the current business process (as is) and business process recommendation (to be), found out that an increase in time analysis reached 12.39% on booking hall events, 4.07% on event implementation, and 6.49% on event evaluation. Beside that, an increase on resource analysis also done with the highest increase 34.54% done by the customer in the event hall ordering business process, 16.44% by community host in the event hall ordering business process, and 8.86% by event manager in the event evaluation business process.